2015
DOI: 10.5007/1980-0037.2015v17n3p257
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da idade relativa na antropometria, maturação biológica e desempenho em jovens futebolistas

Abstract: The study examined the presence of the relative age effect (RAE) and association between birth quartile and anthropometry, biological maturation and physical and technical performance of young Brazilian soccer players. The sample included 119 male players, 74 of U-15 category and 45 of U-17 category, which were divided into quartiles according to the birth year. Biological maturation was assessed using the method of skeletal age of Fels. Anthropometric measurements included body weight, stature and subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The similar anthropometric and physiological characteristics among BQ were in agreement with the absence of RAE in the present study. This relationship has been examined previously in soccer, where some studies supported an association between BQ and these characteristics, i.e., “early born” showed superior characteristics than “late born” (Pedretti and Seabra, 2015; Altimari et al, 2018), whereas other studies did not observe differences (De Oliveira Matta et al, 2015; Junior et al, 2015; Lovell et al, 2015; Skorski et al, 2016; Peña-González et al, 2018). An explanation of the similar anthropometric and physiological characteristics among BQ might be the role of maturation as a covariate (Lovell et al, 2015; Peña-González et al, 2018).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The similar anthropometric and physiological characteristics among BQ were in agreement with the absence of RAE in the present study. This relationship has been examined previously in soccer, where some studies supported an association between BQ and these characteristics, i.e., “early born” showed superior characteristics than “late born” (Pedretti and Seabra, 2015; Altimari et al, 2018), whereas other studies did not observe differences (De Oliveira Matta et al, 2015; Junior et al, 2015; Lovell et al, 2015; Skorski et al, 2016; Peña-González et al, 2018). An explanation of the similar anthropometric and physiological characteristics among BQ might be the role of maturation as a covariate (Lovell et al, 2015; Peña-González et al, 2018).…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, the aim of the present study was to examine (a) the prevalence of RAE in selected and non-selected female volleyball players, and (b) the relationship of RAE with anthropometric and physiological characteristics. Based on relevant research in soccer (Buchheit et al, 2014; De Oliveira Matta et al, 2015), it was hypothesized that RAE would be observed in volleyball players, “early born” would have superior anthropometric and physiological characteristics than “late born” volleyball players, and RAE would have larger magnitude in selected than non-selected volleyball players. For the purpose of this study, “selected” referred to volleyball players who were selected by national team coaches to be considered for the national team of their age group.…”
Section: Introductionmentioning
confidence: 99%
“…Computation of YYIR2 test global means, SDs and quantiles (Figure 3) involved 116 studies/subgroups reporting on 2,478 participants (median age = 23.2 years, IQR = 20.7–26.0 years) (Young et al, 2005; De Souza et al, 2006; Krustrup et al, 2006; Thomas et al, 2006; Mohr et al, 2007, 2016; Iaia et al, 2008, 2015, 2017; Morton et al, 2009; Rampinini et al, 2010; Rebelo et al, 2010; Thomassen et al, 2010; Christensen et al, 2011; Chuman et al, 2011; Mooney et al, 2011, 2013a,b; Roberts et al, 2011; Ueda et al, 2011; Gunnarsson et al, 2012; Ingebrigtsen et al, 2012, 2013, 2014; Nakamura et al, 2012; Saunders et al, 2012; Wells et al, 2012, 2014; Bassini et al, 2013; Buchheit et al, 2013; McGawley and Andersson, 2013; Mohr and Krustrup, 2013, 2014, 2016; Owen et al, 2013; Pivovarniček et al, 2013; Yuki et al, 2013; Fanchini et al, 2014; Karavelioglu et al, 2014; Lollo et al, 2014; Miloski et al, 2014; Nunes et al, 2014; Sampaio et al, 2014; Skovgaard et al, 2014; Brocherie et al, 2015a,b; Cholewa et al, 2015; Coelho et al, 2015; Gatterer et al, 2015; Hogarth et al, 2015a,b; Jamurtas et al, 2015; Krustrup and Mohr, 2015; Leme et al, 2015; Mara et al, 2015; Matta et al, 2015; McLean et al, 2015; Michalsik et al, 2015; Mohr, 2015; Rogan, 2015; Stein et al, 2015; Boer and Van Aswegen, 2016; Bouaziz et al, 2016; Chan et al, 2016; Inness et al, 2016; Joo, 2016; Kilit and Arslan, 2016; Lockie et al, 2016a,b,...…”
Section: Resultsmentioning
confidence: 99%
“…O processo fisiológico de crescimento e desenvolvimento na infância e adolescência produz alterações morfológicas e funcionais que se refletem no perfil de aptidão física nessa faixa etária (1)(2)(3)(4)(5). Essas modificações podem afetar algumas qualidades físicas e habilidades motoras essenciais na prática do futebol e outras atividades esportivas (6)(7)(8)(9).…”
Section: Introductionunclassified